Use of representational difference analysis to reveal differences between truncated leaf syndrome and normal oil palm ramet - Silvarajoo, Kanagamalar (2015)
Truncated Leaf Syndrome (TLS) is a commonly found abnormality amongst tissue cultured plantlets of oil palm (Elaies guineensis Jacq.) which, if severe, will eventually lead to the death of the ramets. It was hypothesized that this phenotype could be due to genetic or epigenetic variability. The first part of this study was aimed to identify the genetic variability via Genomic-Representational Difference Analysis (G-RDA), a technique whereby the differences between two closely related genomes can be identified. In this part, 2 clones of oil palm ramets (1181; severe vs normal and 2751; mild vs normal) were used as starting material with 4 rounds of forward and reverse G-RDA were performed. A total of 18 unique sequences from G-RDA were successfully obtained. Primers were designed and verification of forward G-RDA products through PCR analyses and sequence comparison was carried out using 12 clones of TLS and normal oil palm ramets. Two out of 18 set of primers [F4(6)-1181Bgl and F4(10)-1181Bgl] were identified as potential markers and further verified by PCR and Southern analyses. The primer set F4(6)-1181Bgl was only able to distinguish between TLS and normal ramets of only one genotype (Yangambi) with the presence of expected band in TLS but was absent in normal ramets. The primer set F4(10)-1181Bgl showed the presence of multiple banding pattern in the genotype of La Me and Yangambi. Analysis of the multiple bands sequences revealed that those sequences represent multiple regions within the same genome, hence it is potentially a polymorphic marker. The 2 primer sets mentioned above could be classified as potential genotype specific primers as it is only functional in selected genotype. The second part of this study was aimed to identify the epigenetic variability via Methylation Sensitive-Representational Difference Analysis (MS-RDA). In this part, 2 rounds of forward and reverse MS-RDA were carried out and a total of 4 differentially methylated sequences with matches to known gene were successfully obtained. Primers were designed based on the 4 target genes namely protein ycf68, 3-ketoacyl-CoA synthase 12, Scarecrow-like protein 9 and Nucleotide-diphospho-sugar transferases superfamily protein and verification process was carried out by Quantitative-PCR to identify the respected expression level in normal and TLS ramets. The relative expression level of uncharacterized protein ycf68 is up-regulated, while 3-ketoacyl-CoA synthase 12, Scarecrow-like protein 9 and Nucleotide-diphospho-sugar transferases superfamily protein were down-regulated in TLS ramets as compared to the normal ramets. Further verification with extensive number of samples is needed to elucidate the potential of the above 2 primer sets from G-RDA and 4 primer sets from MS-RDA to be used as markers across all genotypes of oil palm.